Requirement of functional telomeres for metaphase chromosome alignments and integrity of meiotic spindles - Liu, Lin (Oxford University Press, 2002)
Telomerase deficiency in the mouse eventually leads to loss of telomeric repeats from chromosome ends and to end-to-end chromosome fusions, which result in defects in highly proliferative tissues. We show that telomere dysfunction resulting from telomerase deficiency leads to disruption of functional meiotic spindles and misalignment of chromosomes during meiotic division of oocytes in late-generation (G(4)) mice. However, oocytes from first-generation (G(1)) mice lacking telomerase showed no appreciable telomere dysfunction and exhibited chromosome alignment at the metaphase plates of meiotic spindles, in a manner similar to that of wild-type mouse oocytes. These findings suggest that telomerase does not directly influence chromosome alignment and spindle integrity. Rather, functional telomeres may be involved in mediating metaphase chromosome alignment and maintaining functional spindles during meiotic division.